Advanced polymeric materials for sustainability and innovations - Thottathil, Sajith; Thomas, Sabu; Kalarikkal, Nandakumar; Rouxel, Didier, 1965- (Apple Academic Press, 2019)
"The informative volume discusses recent advancements in the research and development of synthesis, characterization, processing, morphology, structure, and properties of advanced polymeric materials. With contributions from leading international researchers and professors at academic, government and industrial institutions, Advanced Polymeric Materials for Sustainability and Innovations has a special focus on eco-friendly polymers, polymer composites, nanocomposites, and blends and materials for traditional and renewable energy. In this book the relationship between processing-morphology-property-applications of polymeric materials is well established. Recent advances in the synthesis of new functional monomers has shown strong potential in generating better property polymers from renewable resources. Fundamental advances in the field of nanocomposites, blends and nanostructured polymeric materials in automotive, civil, biomedical and packaging/coating applications are the highlights of this book"--Resumé vydavatele
Keywords: polymery; polymerní materiály; polymerní kompozitní materiály; environmentálně vhodné technologie; polymers; polymer materials; polymer composite materials; green technology; sborníky; papers of several authors